Computed Tomographic Features of Thymus in Dogs: Correlation with Age, Gender, Breed and Body Fat Content - Mohammad Molazem; Sarang Soroori; Alireza Bahonar; Saghar Karimi (Veterinary Sciences, 2023)
Background: The thymus is the first lymphoid organ formed to regulate a newborn’s immunity. It reaches its maximum size during puberty, after which it undergoes an atrophic procedure called involution, but its ability to grow again in response to some stresses, such as infections, neoplasia, surgeries, chemotherapy, and radiotherapy is maintained. There is no comprehensive study on computed tomographic features of thymus in dogs. So, the goal of the present study is to gain better insight into the thymus using computed tomography as a non-invasive method. Methods: One hundred and fifty dogs classified in five age groups and five breed groups were recruited to this study and the thymus was evaluated using a 2-slice computed tomography machine. The inclusion criteria for the present study were having a normal complete blood count, plain and post-contrast CT scan examination of the thoracic region and no history of neoplasia, chemotherapy or radiotherapy. The visibility, density, enhancement, grade, size, volume, shape, borders and lateralization of the thymus were evaluated and statistical analysis was performed. The effect of obesity on thymic grade and volume was also investigated. Results: The visibility, density, dorsal length, volume and grade decreased with increasing age. The thymic shape and lateralization were mostly wedge shaped and left sided, respectively. The borders became concave with aging and increasing body fat content caused an increase in the fatty degeneration of the thymus. Conclusions: Declining thymic density, grade, size and volume with aging are related to thymic involution and fatty degeneration was accelerated by increasing body fat content. Females and males were different only in thymic shape and small and large breeds were different only in thymic volume. The thymus was visible in some geriatric dogs with no underlying disease. We expect that the present work can be used by radiologists in reading thoracic computed tomography but investigation of thymic characteristics in dogs with neoplasia and history of chemotherapy, radiotherapy and thoracic surgeries can complete this study.